Early arrival of predators controls Aphis spiraecola colonies in citrus clementines - Gómez-Marco, Francesc; Tena, Alejandro; Jaques, Josep A.; Urbaneja, Alberto (Springer, 2020)
Aphis spiraecola Patch. (Hemiptera: Aphididae) is a key pest of citrus clementines. This aphid colonizes tender clementine shoots in the spring and causes important economic losses. A complex of predators preys on A. spiraecola colonies but does not result in satisfactory control. To disentangle the reasons for this failure, we investigated the effect of predators on A. spiraecola colonies and damage over a 3-year period. A. spiraecola colonies were tracked every 48–72 h from the period of aphid colonization until the colony declined or disappeared. The number of aphids, their stage and the presence of predators were recorded in each colony. Different life parameters of A. spiraecola colonies (maximum number of aphids, longevity and colony phenology) varied among the orchards over 3 years. Predators attacked one-third of the colonies, and this did not significantly differ among orchards for the years studied. The maximum number of aphids and longevity of A. spiraecola colonies were not related to the ratio of colonies attacked by predators but were negatively correlated with the time of their first attack. More importantly, the percentage of shoots occupied by A. spiraecola remained below or close to the intervention threshold when colonies were attacked prior to *200 degree days from the beginning of the aphid colonization. These results suggest that (1) the presence of predators at the beginning of the season should be considered to develop new intervention thresholds and (2) biological control programs should promote the early presence of predators in clementine orchards.